Determinasi Kinerja Karyawan Dan Organizational Citizenship Behavior: Analisis Motivasi Kerja Dan Kepemimpinan (Studi Kasus pada Karyawan Swasta di Kota Padang) - Charli, Chintya Ones; Sopali, Mardhatila Fitri (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
This research is aimed at revealing the influence of Work Motivation and Leadership on Employee Performance through Organizational Citizenship Behavior as an Intervening variable. The research was carried out at the Padang City Tourism Office. The research population was 235 employees who worked at the Padang City Tourism Office, both civil servants and honorary employees. Furthermore, 235 employees became the research sample which was taken proportionally and randomly using the proportional random sampling technique. Structural equation modeling (SEM) with a partial least squares (PLS) approach was applied as a data analysis method. The research results revealed that Work Motivation, Leadership did not have a positive and insignificant effect on Organizational Citizenship Behavior, then Work Motivation, Leadership and Organizational Citizenship Behavior had a positive and significant effect on Employee Performance, then there was an influence of Work Motivation on Employee Performance through Organizational Citizenship Behavior. And it is not proven that there is an influence of Leadership on Employee Performance through Organizational Citizenship Behavior.